2022
DOI: 10.1107/s2052520622003766
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular structures of two copper complexes with the pharmaceuticals norfloxacin and tinidazole, when powder X-ray diffraction assists multi-domain single-crystal X-ray diffraction

Abstract: The crystal structures of bis[1-ethyl-6-fluoro-4-oxo-7-(piperazin-1-ium-4-yl)-1,4-dihydroquinoline-3-carboxylato]copper(II) sulfate heptahydrate, [Cu(C16H18FN3O3)2]SO4·7H2O or [Cu(nor)2]SO4·7H2O (nor is norfloxacin), and bis{1-[2-(ethylsulfonyl)ethyl]-2-methyl-5-nitroimide}dinitratocopper(II), [Cu(NO3)2(C8H13N3O4S)2] or [Cu(NO3)2(tnz)2] (tnz is tinidazole), were solved by X-ray diffraction. Both complexes crystallize in the space group P21/c, with Z = 4 (for nor) and Z = 2 (for ntz) molecules per unit cell. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Compared with the raw materials TNZ, 2,6-DHBA, 4-MAC, and 5-C-2-HBA, the characteristic peaks in compounds 1-3 are red-shifted or blue-shifted due to the formation of hydrogen bonds. For instance, the C = N [37] stretching band at 1642 cm −1 and the characteristic peaks of the benzene ring [38] at 1585 cm −1 , 1504 cm −1 , and 1450 cm −1 are respectively blue-shifted or red-shifted in compound 1 compared with the C = N stretching band of 1630 cm −1 in pure TNZ or the characteristic framework vibrations peaks 1631 cm −1 , 1579 cm −1 and 1468 cm −1 of the benzene ring in pure 2,6-DHBA. The IR analysis showed that compounds 1-3 are composed of TNZ and 2,6-DHBA, 4-MAC, and 5-C-2-HBA, respectively, and the interactions between them are hydrogen bonds, which was confirmed by the crystal structure analysis (Figure S1).…”
Section: Ir Analysismentioning
confidence: 99%
“…Compared with the raw materials TNZ, 2,6-DHBA, 4-MAC, and 5-C-2-HBA, the characteristic peaks in compounds 1-3 are red-shifted or blue-shifted due to the formation of hydrogen bonds. For instance, the C = N [37] stretching band at 1642 cm −1 and the characteristic peaks of the benzene ring [38] at 1585 cm −1 , 1504 cm −1 , and 1450 cm −1 are respectively blue-shifted or red-shifted in compound 1 compared with the C = N stretching band of 1630 cm −1 in pure TNZ or the characteristic framework vibrations peaks 1631 cm −1 , 1579 cm −1 and 1468 cm −1 of the benzene ring in pure 2,6-DHBA. The IR analysis showed that compounds 1-3 are composed of TNZ and 2,6-DHBA, 4-MAC, and 5-C-2-HBA, respectively, and the interactions between them are hydrogen bonds, which was confirmed by the crystal structure analysis (Figure S1).…”
Section: Ir Analysismentioning
confidence: 99%